AI-ASSISTED ART THERAPY THROUGH DIGITAL PLATFORMS - Akhare, Vishakha; Mundada, Kapil; Arivukkodi R; Gupta, Shikha; Patil, Tejal H.; Patil, Balkrishna K (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Digital-based AI-assisted art therapy is a novel discursive field of application of intelligent computing that combines psychological theory, creative practice, and intelligent computing to provide additional mental health services. In the current paper, the author offers a detailed map of how art therapy can be provided through AI-mediated digital space and focuses particularly on emotional expression, reflective interaction, and therapist-mediated intervention. Based on the concepts of expressive and humanistic art therapy, the proposed solution draws on the affective computing and human-computer interaction theories to convert artistic pieces into valuable emotional clues. Machine learning models are used to identify emotion and analyse affect in multimodal inputs, such as drawings, paintings, text stories, and interaction behavior. Guided visual creation is also assisted by generative AI systems, where users are able to express themselves emotionally by means of adaptive prompts, styles and symbolic forms, and reflectively communicate through natural language processing and story generation. They are suggested to have a structured workflow of therapeutic elements that include onboarding, baseline emotional profiling, adaptive creative sessions, and longitudinal visualisation of emotional progress. The application cases show that AI-assisted art therapy has the potential to be used in anxiety, stress management, depression, and neurodiverse users, as well as in remote community-based mental health care.